(x-3-3i)*(x-3+3i)=

Simple and best practice solution for (x-3-3i)*(x-3+3i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3-3i)*(x-3+3i)= equation:


Simplifying
(x + -3 + -3i)(x + -3 + 3i) = 0

Reorder the terms:
(-3 + -3i + x)(x + -3 + 3i) = 0

Reorder the terms:
(-3 + -3i + x)(-3 + 3i + x) = 0

Multiply (-3 + -3i + x) * (-3 + 3i + x)
(-3(-3 + 3i + x) + -3i * (-3 + 3i + x) + x(-3 + 3i + x)) = 0
((-3 * -3 + 3i * -3 + x * -3) + -3i * (-3 + 3i + x) + x(-3 + 3i + x)) = 0
((9 + -9i + -3x) + -3i * (-3 + 3i + x) + x(-3 + 3i + x)) = 0
(9 + -9i + -3x + (-3 * -3i + 3i * -3i + x * -3i) + x(-3 + 3i + x)) = 0

Reorder the terms:
(9 + -9i + -3x + (9i + -3ix + -9i2) + x(-3 + 3i + x)) = 0
(9 + -9i + -3x + (9i + -3ix + -9i2) + x(-3 + 3i + x)) = 0
(9 + -9i + -3x + 9i + -3ix + -9i2 + (-3 * x + 3i * x + x * x)) = 0

Reorder the terms:
(9 + -9i + -3x + 9i + -3ix + -9i2 + (3ix + -3x + x2)) = 0
(9 + -9i + -3x + 9i + -3ix + -9i2 + (3ix + -3x + x2)) = 0

Reorder the terms:
(9 + -9i + 9i + -3ix + 3ix + -9i2 + -3x + -3x + x2) = 0

Combine like terms: -9i + 9i = 0
(9 + 0 + -3ix + 3ix + -9i2 + -3x + -3x + x2) = 0
(9 + -3ix + 3ix + -9i2 + -3x + -3x + x2) = 0

Combine like terms: -3ix + 3ix = 0
(9 + 0 + -9i2 + -3x + -3x + x2) = 0
(9 + -9i2 + -3x + -3x + x2) = 0

Combine like terms: -3x + -3x = -6x
(9 + -9i2 + -6x + x2) = 0

Solving
9 + -9i2 + -6x + x2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9i2 + -6x + -9 + x2 = 0 + -9

Reorder the terms:
9 + -9 + -9i2 + -6x + x2 = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -9i2 + -6x + x2 = 0 + -9
-9i2 + -6x + x2 = 0 + -9

Combine like terms: 0 + -9 = -9
-9i2 + -6x + x2 = -9

Add '6x' to each side of the equation.
-9i2 + -6x + 6x + x2 = -9 + 6x

Combine like terms: -6x + 6x = 0
-9i2 + 0 + x2 = -9 + 6x
-9i2 + x2 = -9 + 6x

Add '-1x2' to each side of the equation.
-9i2 + x2 + -1x2 = -9 + 6x + -1x2

Combine like terms: x2 + -1x2 = 0
-9i2 + 0 = -9 + 6x + -1x2
-9i2 = -9 + 6x + -1x2

Divide each side by '-9'.
i2 = 1 + -0.6666666667x + 0.1111111111x2

Simplifying
i2 = 1 + -0.6666666667x + 0.1111111111x2

Reorder the terms:
-1 + i2 + 0.6666666667x + -0.1111111111x2 = 1 + -0.6666666667x + 0.1111111111x2 + -1 + 0.6666666667x + -0.1111111111x2

Reorder the terms:
-1 + i2 + 0.6666666667x + -0.1111111111x2 = 1 + -1 + -0.6666666667x + 0.6666666667x + 0.1111111111x2 + -0.1111111111x2

Combine like terms: 1 + -1 = 0
-1 + i2 + 0.6666666667x + -0.1111111111x2 = 0 + -0.6666666667x + 0.6666666667x + 0.1111111111x2 + -0.1111111111x2
-1 + i2 + 0.6666666667x + -0.1111111111x2 = -0.6666666667x + 0.6666666667x + 0.1111111111x2 + -0.1111111111x2

Combine like terms: -0.6666666667x + 0.6666666667x = 0.0000000000
-1 + i2 + 0.6666666667x + -0.1111111111x2 = 0.0000000000 + 0.1111111111x2 + -0.1111111111x2
-1 + i2 + 0.6666666667x + -0.1111111111x2 = 0.1111111111x2 + -0.1111111111x2

Combine like terms: 0.1111111111x2 + -0.1111111111x2 = 0.0000000000
-1 + i2 + 0.6666666667x + -0.1111111111x2 = 0.0000000000

The solution to this equation could not be determined.

See similar equations:

| 0=x^2+4x+12 | | x^2+7x=68.75 | | 5x+2y+2=11+9y-x | | 13-ln(5-x)=0 | | 7=5v-19 | | -54=7x+3x+6 | | 2x-4=(2x-9)/2 | | -12=-6j | | 2g-11(-2)=26 | | 0=-6x-2x-8 | | Dy=Cx | | 4/3t=5/2 | | -6x-9+2x=39 | | (3t^2-t-4)(4t^2+3t-1)= | | 2x+5+3x=-25 | | 3(13+5.5k)=6k+18 | | 33=-4x-3x-2 | | -2-3x-4x=33 | | Cot^4x-1=0 | | 2-3x-4x=33 | | 2x^2+6y^2=13 | | 49/7p-49 | | 4[lnz+ln(z+5)]-2ln(z-5)= | | h=-16t*t+128t | | 4+6x+6x=-44 | | 1+7x+2x=109 | | 7(c-9)=9(2c-8)-4c | | 9x^6y^10/x^0Y^9 | | y=a^8+cos^8x | | n=c-m | | 3t+nt=y | | -4x+9+5x=18 |

Equations solver categories